Application of capillary immunoelectrophoresis revealed an age‐ and gender‐dependent regulated expression of PrPC in liver. Issue 24 (9th November 2015) - Arora, Amandeep Singh; Zafar, Saima; Kollmar, Otto; Llorens, Franc; Tahir, Waqas; Vanselow, Sven; Kumar, Prateek; Schmerr, Mary Jo; Schmitz, Matthias; Zerr, Inga
Abstract : The cellular prion protein (PrPC) is a glycoprotein, anchored to the plasma membrane and abundantly expressed in the central nervous system. The expression of PrPC in the peripheral tissues is low and only little information is available on its functions in the nonneuronal tissues. The antioxidant function of PrPC during the activation of hepatic stellate cells has already been reported. Therefore, the aim of the study was to expand our knowledge on the functions of PrPC by detailed characterization of its expressional profile in the liver. In a combined strategy by using capillary immunoelectrophoresis and standard techniques, we have shown a sexually dimorphic expression of PrPC in mice and human liver tissues. Further, we showed a significant age‐dependent upregulation of PrPC expression in the liver of 14‐ and 9‐month‐old mice as compared to 3 months of age. Therefore, this study may provide new insights into the gender‐specific role of PrPC in the liver, which may further be linked to its protective role against oxidative stress during aging. In addition, the current study also shows an application of immunoelectrophoresis with a low coefficient of variation to analyze the miniscule amount of PrPC in the mouse liver tissue.